Buckling resistance of the wall of a steel grain silo - Marcinowski, Jakub; Sakharov, Volodymyr (Archives of Civil Engineering, 2026)
The walls of steel grain silos are susceptible to buckling. The reason for this undesirable phenomenon is the vertical impact of grain stored in the silo on the walls, most often made of corrugated sheet metal with horizontal corrugations. External, vertical stiffeners make a wall strengthened and together with corrugated sheet metals create orthogonal shell structure. The procedures included in the applicable standards make it possible to estimate the buckling load capacity of the wall of a silo constructed in this way. The paper presents an example of the analysis of the buckling load capacity of the wall of a steel silo with a capacity of 700 m3. Two of the methods recommended in applicable standards were used. Numerical simulations were also performed to determine the critical level of load intensity. The analyses carried out allowed conclusions to be drawn regarding the buckling load capacity of the wall of the analysed silo.
Keywords: analytical calculations; buckling resistance; corrugated steel sheet; numerical simulations; steel silo; wall stiffeners